Influence of temperament and anxiety on athletic performance - Han, D. H.; Kim, J. H.; Lee, Y. S.; Bae, S. J.; Bae, S. J.; Kim, H. J.; Sim, M. Y.; Sung, Y. H.; Lyoo, I. K. (Journal of Sports Science & Medicine, 2006)
Our research aimed to conduct basic descriptions of temperamental traits and the level of state and trait anxiety of young male athletes, and to compare them by type of sports. Study participants were 277 athletes and 152 non-athletes who were all high school boys. The Korean version of the Temperament and Character Inventory (TCI) was used for checking temperamental traits while the Korean version of the State and Trait Anxiety Inventory form Y (STAI-KY) was used to estimate anxiety levels. Harm Avoidance score of athletes was higher than that of non-athletes. Harm Avoidance score of golfers was lowest and that of swimmers was highest. The state anxiety score of baseball players was lowest and that of Taekwondo players was highest. The trait anxiety score of baseball players was also lowest and that of golfers was highest. Both trait and state anxieties of the 'winner' group were lower than those of the 'no winner' group. While prior research mainly focused on athletes' environment and phenotypic characteristics, we studied the pattern of temperaments in athletes along with its potential influence on athletic performance.